Legislar en la América hispánica en la temprana edad moderna : procesos y características de la producción de los Decretos del Tercer Concilio Provincial Mexicano (1585) - Moutin, Osvaldo Rodolfo (Global perspectives on legal history, 2016)
"The decrees of the Third Mexican Provincial Council, celebrated in 1585, had an important impact on the organization of the colonial Church and Spanish-American society, from the time they were published in 1622 until the nineteenth century. This research focuses on how the decrees were drafted, taking into consideration the working materials used in the conciliar meeting room by the bishops and their assistants, and thus highlighting the intentions of the conciliar fathers in their new and original elaboration of both Canon Law and Derecho Indiano"--